2017
DOI: 10.3389/fevo.2017.00100
|View full text |Cite
|
Sign up to set email alerts
|

The Right Tools for the Job: Cooperative Breeding Theory and an Evaluation of the Methodological Approaches to Understanding the Evolution and Maintenance of Sociality

Abstract: Why do we observe so many examples in nature in which individuals routinely delay or completely forgo their own reproductive opportunities in order to join and remain within a group? Cooperative breeding theory provides a rich framework with which to study the factors that may influence the costs and benefits of remaining philopatric as a non-breeder. This is often viewed as an initial step in the development of costly helping behavior provided by non-breeding subordinates. Despite many excellent empirical stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 163 publications
(300 reference statements)
0
15
0
Order By: Relevance
“…Of the marine taxa tested so far, habitat-specialist coral-reef fishes are emerging as a useful model species to study theories of social evolution and maintenance [20, 27, 28] and have shown similar responses to habitat manipulation as terrestrial species (e.g. [23]).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the marine taxa tested so far, habitat-specialist coral-reef fishes are emerging as a useful model species to study theories of social evolution and maintenance [20, 27, 28] and have shown similar responses to habitat manipulation as terrestrial species (e.g. [23]).…”
Section: Introductionmentioning
confidence: 99%
“…These two hypotheses are often viewed as two sides of the same coin as they both look at aspects of ecology to explain social evolution and maintenance [ 20 ]. The benefits of philopatry hypothesis focuses on the benefits conferred from residing in a high-quality habitat (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…While there is extensive observational and experimental evidence demonstrating that high relatedness, future benefits and ecological constraints help explaining non-breeding behaviors in animal societies, relatively limited work has been done to investigate the roles of social constraints 20 . Furthermore, there is a real need to broaden the diversity of social taxa and types of cooperative behaviors considered, so that we may better understand the drivers of social group formation across taxa and along the continuum from simple to complex eusocial systems 21 , 22 .
Fig.
…”
Section: Introductionmentioning
confidence: 99%